Comprehensive review on cardiac manifestation of scrub typhus - Sivasubramanian, Barath Prashanth; Abdul Khader, Abul Hasan Shadali; Ravikumar, Diviya Bharathi; Dominic Savio, Francis Vino; Thirupathy, Umabalan; Thiruvadi, Varshini; Prasad, Rhea; Thokala, Hema; Qadeer, Husna; Venkataperumal, Dhiraj Poragal; Gupta, Ashima; Honganur, Nagaraj Sanchitha; et al. (Frontiers in Tropical Diseases, 2024)
Scrub typhus, a zoonotic disease caused by Orientia tsutsugamushi and transmitted by chiggers, predominantly affects the Asia-Pacific region. Complications of Scrub Typhus involve multiple systems, including cardiovascular (pericarditis, arrhythmia, myocarditis), respiratory (acute respiratory distress syndrome), hepatic (hepatitis), and renal (azotemia). In this review, we comprehensively focused on the cardiac manifestations caused due to scrub typhus. Scrub typhus-induced pericarditis should be suspected in patients residing in endemic regions presenting with fever, thrombocytopenia, and pericardial effusion. If undetected, it frequently leads to cardiomegaly, pericardial effusion, and congestive heart failure. Heart failure with scrub typhus commonly occurs following myocardial inflammation, particularly in patients with pre-existing cardiac disorders. Scrub typhus myocarditis is a relatively rare, but serious cardiac complication with a high mortality rate of up to 24.0%. Arrhythmias arise due to the involvement of the interventricular septum, coronary artery, or cardiac valves causing variable ECG findings including sinus arrhythmia, T wave changes, and QTc interval prolongation. Atrial fibrillation due to scrub typhus is associated with a 1.3 fold increase in 3-month mortality. These cardiac complications are mainly assessed using electrocardiography (ECG) and echocardiography. Serology is the primary diagnostic tool for O. tsutsugamushi. While the Scrub Typhus Detect IFA test offers 100% sensitivity, the Weil Felix test is specific and cost-effective. Nested PCR and ELISA are effective for early detection but are limited to resource-rich settings. Diagnostic difficulties arise from nonspecific symptoms and current testing limitations. Vaccine development using extracellular vesicles, nanoparticles, and subunit vaccines shows promise. Combined therapy with doxycycline and azithromycin is recommended for cardiac complications, alongside guideline-directed therapy. The review underscores the need for heightened clinical awareness and prompt management of scrub typhus, especially in endemic regions. It also highlights the necessity for further research into the pathogenesis of cardiac involvement and the development of more effective diagnostic tools and treatments.